How overconfidence influences entrepreneurship - Ioannis S. Salamouris (Journal of Innovation and Entrepreneurship, 2013)
The only thing certain in economic life is that most of it is conducted into an uncertain environment; that raises a question though: what makes individuals pursue entrepreneurship which engages too much risk for an unsure, or too little, return? Research has shown that people tend to be optimistic when a decision is made under uncertainty (Taylor and Brown, Psychological Bulletin, 103:193-210, 1988) and exhibit overconfidence in judgment (DeBondt and Thaler 1995). Overconfident individuals tend to overestimate their relative ability (Svenson, Acta Psychologica 47:143-148, 1981); therefore, their perception about their actions, probabilistically, appears to them to be safer than that of others who exhibit no overconfidence. A sample of 2,994 entrepreneurs provides us with interesting findings (Cooper et al., Journal of Business Venturing 3:97-108, 1988): 81% consider their chances of success to be at least 70%, and 33% believe their chances of success to reach a probability of 100%. In reality, about 75% of new businesses no longer exist after 5 years. Is it that entrepreneurs are incapable of seeing the risk or/and measure it, or is it that they consciously perceive a different dimension of risk involved in their actions? A more recent study (Wu and Knott, Management Science 52:1315-1330, 2006) showed, in general, that entrepreneurs are more cautious than most of us would think or believe, and the belief that entrepreneurs have bigger tolerance for risk is rather unsupported according to their findings. Although there are some cases where entrepreneurs appear to be more risk averse than average, still it does not prevent them to bear risk. Such finding sounds controversial, but in reality it is not. Entrepreneurs seem to set different dimensions for uncertainty; thus, the oxymoron suggested above actually justifies their actions. Entrepreneurs believe that uncertainty has two dimensions: the market uncertainty and the uncertainty regarding ability. Similar to the majority of people, entrepreneurs detest the market risk but, on the other hand, they much appreciate their own abilities(overconfidence) that compensate for their dislike of risk. The purpose of this paper is to highlight the impact of overconfidence in entrepreneurial behavior.
Keywords: 650; entrepreneurship overconfidence; uncertainty; behavior